Dampak Penggunaan Gadget Terhadap Interaksi Sosial Anak Usia Pendidikan Dasar : Dampak Penggunaan Gadget Terhadap Interaksi Sosial Anak Usia Pendidikan Dasar - Siti Latifah; Anastasia Adiwirahayu (SOSIO PROGRESIF | Media Pemikiran Studi Pembangunan Sosial, 2022)
The rapid development of technology has brought the world into the modern and advanced era of globalization. In this modern era, humans are required to keep abreast of the times when life is practical, effective, and efficient. The needs of human life are getting more and more complex, therefore tools are created that can help smooth and lighten the burden of human work, one of which is a very popular technology is gadgets. The use of gadgets in children of primary education age is one of the social problems that exist in society. It is feared that the use of these gadgets will cause dependence on children and have a negative impact on children, such as social interactions of children being disturbed while playing gadgets and children becoming indifferent to their surroundings. The purpose of this study was to determine the patterns and impacts of using gadgets on the social interactions of primary education aged children in Kampung Bogem. The research method used is descriptive qualitative with interviews as a research instrument. The results showed the negative impact of gadget use experienced by children of primary education, namely forgetfulness of time, laziness, addiction to gadgets, indifference to the environment and disturbed social interactions, while the positive impact of using gadgets is that it adds broader insight and facilitates children's learning media.Keywords: gadget impact, social interaction